Currículo, arte e formação continuada: percepções de arte-educadores participantes do programa "A rede aprende com a rede" no Estado de São Paulo - Silva, Irinéia Aparecida dos Santos (2011)
This research examines some perceptions of art teachers who teach in state schools in the region of Franco da Rocha , São Paulo, on the application of the "Network Learns Network , focusing on the intent of the course that had as an objective to clarify and deepen. Course of Art of São Paulo . The epistemological grounding of this research is based on theoretical frameworks that expand the field of study in relation to Continuing Education, Curriculum, Art and Ethics. Indispensable categories in the current educational context, its discussion, reflection and discussion assume prospects for significant improvements in the school universe. For its implementation we chose to follow the methodological guidelines of Cognitive Mapping, proposed in 2006 by the researcher Alexandra L. Pereira Okada and analysis of the perceptions of art teachers surveyed and had as theoretical authors Orlandi (1989) and Chizzotti (2008). It is expected that the reflection of this work will contribute to the educational practice of the art educator in making the art a cognitive learning, sensitizing, humanizing and liberating to its students